2014
DOI: 10.1002/psc.2660
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐biocompatibility of conjugates designed by chemical similarity

Abstract: The roughness and thickness of films formed by hybrid conjugates prepared by coupling poly(3,4-ethylenedioxythiophene) and synthetic amino acids bearing a 3,4-ethylenedioxythiophene group in the side chain have been significantly increased using a new synthetic approach. This procedure also provoked a more effective incorporation of the amino acid at the end of the polymer chains, as has been reflected by the electronic and electrochemical properties. Although the surface polarity of all these materials is sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…28 In the first step, which is the same for the two strategies ( Figure 2), PEDOT films were deposited onto steel sheets by chronoamperometry (CA) under a constant potential of 1.40 V and using a 10 mM 3,4-ethylenedioxythiophene (EDOT) solution in acetonitrile containing 100 mM LiClO 4 as supporting electrolyte. The polymerization time (θ 1 ) was only 10 s. After eliminating the excess of monomer and dopant…”
Section: Synthesis Of the Pedot-rg E D Conjugatementioning
confidence: 99%
See 2 more Smart Citations
“…28 In the first step, which is the same for the two strategies ( Figure 2), PEDOT films were deposited onto steel sheets by chronoamperometry (CA) under a constant potential of 1.40 V and using a 10 mM 3,4-ethylenedioxythiophene (EDOT) solution in acetonitrile containing 100 mM LiClO 4 as supporting electrolyte. The polymerization time (θ 1 ) was only 10 s. After eliminating the excess of monomer and dopant…”
Section: Synthesis Of the Pedot-rg E D Conjugatementioning
confidence: 99%
“…The PEDOT-RG E D conjugate was prepared using two alternative strategies (A and B) of three steps each, which are known to provide materials with different surface properties. 28 In the first step, which is the same for the two strategies (Fig. 2), PEDOT films were deposited onto steel sheets by chronoamperometry (CA) under a constant potential of 1.40 V and using a 10 mM 3,4-ethylenedioxythiophene (EDOT) solution in acetonitrile containing 100 mM LiClO 4 as the supporting electrolyte.…”
Section: Synthesis Of the Pedot-rg E D Conjugatementioning
confidence: 99%
See 1 more Smart Citation
“…Evidently, Figure 1 also shows that the larger is the polymerization time, the more extensive is the morphologic homogeneity, showing much regular dispersion when θ = 3 s than when it is 1 s (Figure 1b compared to the former). Nonetheless, a more detailed examination of those regions that have already been covered by polymer at θ = 1 s shows several features yet observed in cases in which polymerization was completed: 32 PEDOT chains tend to organize in a dense distribution of sharp peaks forming two differentiated levels. On the top level, a very small number of high and compact clusters form from the aggregation of peaks, whereas the bottom level involves individual peaks and low clusters of reduced dimensions, which can be associated with most recently formed polymer chains that accumulate at the bottom of the valleys.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…We showed that the conjugates obtained by linking such synthetic amino acids with PEDOT (named PEDOT-I and PEDOT-II in Scheme 1) exhibit electrochemical and electrical activity. Furthermore, cell adhesion and proliferation assays showed that the behavior of both PEDOT-I and PEDOT-II as cellular matrices is better than is PEDOT counterpart, the latter being a well-known electrobiocompatible material [91,95].…”
Section: Introduction To Hybrid Materials Based On Amyloid-pla Conjugatesmentioning
confidence: 99%